Application of Behavioristic Learning Theory in the Development of Islamic Religious Education Curriculum (PAI) - Hafidz, Achmad; Erihadiana, Mohamad; Surya Siregar, Hariman (Yayasan Mentari Madani, 2024)
Behavioristic theory, which focuses on the role of stimulus, response, and reinforcement, has long been the basis for approaches to learning in a variety of scientific disciplines. In the PAI context, the application of behavioristic theory can influence the way students understand and internalize religious values and religious practices. This article outlines the basic concepts of behavioristic theory and explains the main principles that form the basis of this approach. Apart from that, this article also explains the main components in the PAI curriculum, which include learning objectives, teaching materials, learning methods, and assessment of learning outcomes. In the main part of this article, we consider the application of behavioristic theory in the development of PAI curricula. This includes steps such as identifying learning objectives, developing teaching materials that are in accordance with behavioristic principles, selecting behaviorist-oriented learning methods, and methods for assessing learning outcomes that are consistent with this approach. Apart from discussing the benefits and advantages of applying behavioristic theory, this article also identifies the challenges and limitations in applying this approach in the PAI context. Efforts to overcome these obstacles are also discussed, providing guidance for PAI curriculum developers. This research has significant implications for the development of Islamic religious education, especially in the context of the PAI curriculum.